High activity of Ag-doped Cd0.1Zn0.9S photocatalyst prepared by the hydrothermal method for hydrogen production under visible-light irradiation - Leny, Yuliati; Melody, Kimi; Mustaffa, Shamsuddin (Beilstein-Institut., 2014)
Background: The hydrothermal method was used as a new approach to prepare a series of Ag-doped Cd0.1Zn0.9S photocatalysts. The effect of Ag doping on the properties and photocatalytic activity of Cd0.1Zn0.9S was studied for the hydrogen production fromwater reduction under visible light irradiation.